2016
DOI: 10.1163/15685411-00002958
|View full text |Cite
|
Sign up to set email alerts
|

Nematode communities as indicators of the status of a soil ecosystem influenced by mining practices in Brazil

Abstract: This study evaluated the effects of mining practices using soil nematodes as bioindicators. Soil samples represented four different subsystems found in the CeBio Research Center, including natural/undisturbed (rainforest (RF) and savannah (SA)) and disturbed (Eucalyptus spp. (EU) and grassland (GR)) subsystems. Ecological descriptors S (3.5-9.5), d (1.22-4.23) and MI (1.9-3.23) significantly differentiated the subsystem GR (high impact) from the other subsystems. Additionally, poorly covered soil (i.e., subsys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The flora in the Quadrilátero Ferrífero has been studied expensively, especially in iron outcrops, typical ecosystems associated with superficial iron crusts (Carmo and Jacobi, 2013). Studies report the diversity of the fauna (Salvador-Jr et al, 2011), rhizobial communities (Castro et al, 2017), nematodes (Caixeta et al, 2016), and mycorrhizal fungi (Teixeira et al, 2017;Vieira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The flora in the Quadrilátero Ferrífero has been studied expensively, especially in iron outcrops, typical ecosystems associated with superficial iron crusts (Carmo and Jacobi, 2013). Studies report the diversity of the fauna (Salvador-Jr et al, 2011), rhizobial communities (Castro et al, 2017), nematodes (Caixeta et al, 2016), and mycorrhizal fungi (Teixeira et al, 2017;Vieira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Song et al (2017) showed that nematode genera richness increased linearly with soil moisture and plant species richness. Dry periods, as experienced in May of the current study, are known to be characterised by low micro-organism activity (Caixeta et al 2016). This was also the time that the water receded in the wetland leaving large areas of dry vegetation.…”
Section: Nematode Analysismentioning
confidence: 86%
“…Nematode Abundance and Diversity Nematode community structure in soil is closely associated with the surrounding habitat (Lazarova et al 2004;Caixeta et al 2016), and disturbances are known to affect both nematode density and trophic structure (Bongers and Bongers 1 9 9 8 ) . N e m a t o d e s b e l o n g i n g t o t h e g e n u s Tylenchorhynchus, an obligate plant feeder, were found throughout the present study.…”
Section: Nematode Analysismentioning
confidence: 99%
“…The genera Criconema is a plant-parasitic nematode that is very sensitive to environmental disturbances, and its population is favored by soils covered with plants and in those with a high content of organic matter, such as natural vegetation and agroecosystems with low anthropogenic disturbance ( Caixeta et al, 2016 ). The genus Helicotylenchus , which is abundant in the soil of naturally fertilized coffee plantations and the forest fragment, is usually a very common plant-parasitic nematode and is present at high densities in annual and perennial plantations and natural ecosystems ( Tomazini et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%